Influence of Sodium Hydroxide on the Properties of Uncalcined Flue Gas Desulphurization Gypsum-Slag Composite Binder - Jiao, Baoxiang; Jiao, Baolong; Li, Yushou; Li, Yuhua; Guo, Wei; Wu, Song (Asian Journal of Chemistry, 2014)
The composite binder was prepared by adding a small amount of slag and sodium hydroxide to original flue gas desulphurization gypsum. The Influence of sodium hydroxide on the properties and structure of the composite materials with 70 % flue gas desulphurization gypsum and 30 % slag was discussed. The results showed that when the amount of sodium hydroxide was 0.25 %, the setting time of cementitious materials was appropriate and the initial setting time was about 600 min and the cementitious materials got the highest mechanical strength. The flexural and compressive strengths of samples cured at 28 days were 5.1 and 25.8 MPa, respectively. X-Ray diffraction results indicated that ettringite crystals, C-S-H gels and zeolite existed in the hydration products. Scanning electron microscopy results showed that the cementitious materials covered on the surface of gypsum tightly and the microstructure of the sample cured at 28 days was dense.